2010
DOI: 10.1164/rccm.200903-0442oc
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Cognitive and Psychological Outcomes in the Awakening and Breathing Controlled Trial

Abstract: In this trial, management of mechanically ventilated medical ICU patients with a wake up and breathe protocol resulted in similar cognitive, psychological, and functional outcomes among patients tested 3 and 12 months post-ICU. The proven benefits of this protocol, including improved 1-year survival, were not offset by adverse long-term outcomes. Clinical trial registered with www.clinicaltrials.gov (NCT 00097630).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
190
2
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(204 citation statements)
references
References 53 publications
8
190
2
4
Order By: Relevance
“…Attrition is a recognized barrier to conducting long-term outcomes studies in critical care trials (24,25,(57)(58)(59), caused in part by the mortality experienced by critically ill patients. After accounting for mortal losses, the requirement that subjects be enrolled in EA-PAC, and the delay in study initiation, only 406 of the 1,001 subjects randomized in FACTT were alive and eligible for ACOS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Attrition is a recognized barrier to conducting long-term outcomes studies in critical care trials (24,25,(57)(58)(59), caused in part by the mortality experienced by critically ill patients. After accounting for mortal losses, the requirement that subjects be enrolled in EA-PAC, and the delay in study initiation, only 406 of the 1,001 subjects randomized in FACTT were alive and eligible for ACOS.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies need to balance the merits of administering a more comprehensive battery with the potential burden imposed on study participants. Potential solutions to improve retention and test completion in future studies include increasing the flexibility of scheduling by centralizing test administration in different time-zones to minimize potential conflicts with work or healthcare visits; increasing the number of trained staff to administer the neuropsychological battery and identifying and using the most effective strategies to ensure test completion; selecting an intermediate testing time point (e.g., 3 mo), which minimizes mortal losses yet ensures adequate time for survivors to transition through the healthcare system to home (24,25,62,63); using a shorter test battery (64) or limiting the domains to be assessed (62); and using multiple strategies in a systematic fashion to retain participants (60,61). Through the effective use of many of these strategies, more recent studies are demonstrating the ability to recruit and retain survivors of ALI successfully (61,65,66).…”
Section: Discussionmentioning
confidence: 99%
“…In 2010, a prospective follow-up trial by Jackson et al 16 was conducted to evaluate the impact of the ABC trial intervention on cognitive and psychological measures in 80 patients. The results indicated that although less sedation was achieved in the intervention group (as measured by days in coma), the control group had only a slight, nonsignificant increase in the incidence of PTSD (P=.59) at 3 months and no difference at 12 months (P=.97) after discharge (see Table).…”
Section: Effects Of the Intervention On Ptsdmentioning
confidence: 99%
“…Long-term cognitive, psychological, and functional outcomes were subsequently reported for the daily interruption of sedation studies by Kress et al and Girard et al There was no increase in adverse long-term outcomes in patients who received daily interruption of sedation during their ICU stay, including no increase in the incidence of post-traumatic stress disorder. 12,64 Several recent studies have examined whether combining daily interruption of sedation with physical and occupational therapy can reduce long-term complications of critical illness such as ICU-acquired weakness and neuropsychiatric disease. 65,66 In a randomized controlled trial by Schweickert et al, 65 104 mechanically ventilated patients in the ICU were randomly assigned to early exercise and A "no sedation strategy" was studied by Strøm et al 67 in a trial of 140 critically ill adult patients who were randomized to receive either no sedation or sedation (20 mg/mL propofol for 48 h, 1 mg/mL midazolam thereafter) with daily interruption until awake (control group).…”
Section: Concept Of Minimal or "No" Sedationmentioning
confidence: 99%